A review of the Cenozoic stratigraphy and glacial history of the Lambert Graben-Prydz Bay region, East Antarctica - Whitehead, JM; Quilty, PG; McKelvey, BC; O'Brien, PE (2006)
The Cenozoic glacial history of East Antarctica is recorded in part by the stratigraphy of the Prydz Bay-Lambert Graben region. The glacigene strata and associated erosion surfaces record at least 10 intervals of glacial advance (with accompanying erosion and sediment compaction), and more than 17 intervals of glacial retreat (enabling open marine deposition in Prydz Bay and the Lambert Graben). The number of glacial advances and retreats is considerably less than would be expected from Milankovitch frequencies due to the incomplete stratigraphic record. Large advances of the Lambert Glacier caused progradation of the continental shelf edge. At times of extreme glacial retreat, marine conditions reached > 450 km inland from the modern ice shelf edge. This review presents a partial reconstruction of Cenozoic glacial extent within Prydz Bay and the Lambert Graben that can be compared to eustatic sea-level records from the southern Australian continental margin. Â© Antarctic Science Ltd.